A market of radical ideas: consumption and protest in Brazil in 1968: Um mercado de ideias radicais: consumo e protesto no Brasil de 1968 (Revista de História da UEG (REVHIST), 2022)
This article problematizes the imaginary and representations of 1968 from the mass circulation magazines (Veja, Manchete and Realidade). More than an expressive year of political struggles, 1968 articulated new forms of communication that were being consolidated at that time – as is the case with television and its language –, reverberating in the ways and means of contesting and protesting. We understand that these transformations of the protest language and the terms mobilized by the youth of the period can be accessed and problematized from the magazines, understood as products of the consumer society and active agents in the mobilization of symbols that constituted the political events and the concept of 1968, marking it with its own aesthetic, sometimes ignored in favor of its most salient political conflicts. Thus, we highlight the articulation between social claims, consumption and communication vehicles of great circulation in Brazil in 1968.Keywords: 1968. Consumption. Protest. Concept. Youth.